2011
DOI: 10.1371/journal.pone.0027221
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus-Mediated Rescue of the Cognitive Defects in a Mouse Model for Angelman Syndrome

Abstract: Angelman syndrome (AS), a genetic disorder occurring in approximately one in every 15,000 births, is characterized by severe mental retardation, seizures, difficulty speaking and ataxia. The gene responsible for AS was discovered to be UBE3A and encodes for E6-AP, an ubiquitin ligase. A unique feature of this gene is that it undergoes maternal imprinting in a neuron-specific manner. In the majority of AS cases, there is a mutation or deletion in the maternally inherited UBE3A gene, although other cases are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 29 publications
8
85
0
Order By: Relevance
“…The finding that LTP could be fully recovered at all ages is consistent with previous findings showing that the hippocampal LTP deficit in adult AS mice is reversible upon acute pharmacological treatment with an ErbB inhibitor or with ampakine cognitive enhancers (18,19). However, expression of UBE3A in adult Ube3a m-/p+ mice through a viral-mediated approach only partially recovered synaptic plasticity (20). This apparent discrepancy likely reflects the limited efficiency of in vivo virally mediated neuronal transduction, compared with the more homogeneous biodistribution of systemically administered pharmacological compounds.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that LTP could be fully recovered at all ages is consistent with previous findings showing that the hippocampal LTP deficit in adult AS mice is reversible upon acute pharmacological treatment with an ErbB inhibitor or with ampakine cognitive enhancers (18,19). However, expression of UBE3A in adult Ube3a m-/p+ mice through a viral-mediated approach only partially recovered synaptic plasticity (20). This apparent discrepancy likely reflects the limited efficiency of in vivo virally mediated neuronal transduction, compared with the more homogeneous biodistribution of systemically administered pharmacological compounds.…”
Section: Discussionsupporting
confidence: 91%
“…Transcriptional upregulation has been approached by both gene therapy141 and pharmacologic intervention 142. Daily et al showed that direct injection of a recombinant adeno- associated viral vector carrying Ube3a into the hippocampi of adult AS mice could significantly improve associative learning (contextual fear conditioning) 141.…”
Section: Status Of Basic Researchmentioning
confidence: 99%
“…The AS mouse model has been used extensively for testing potential drugs and gene therapies for treating AS (13,14). One therapeutic approach has been to identify proteins that are upregulated in the brains of AS mice and to then search for pharmacological agents that target the expression or activity of the up-regulated protein.…”
mentioning
confidence: 99%
“…In addition, AS mice display defects in learning and memory, motor coordination, locomotor activity (14,17,20,21), and an increased number of seizures when exposed to an audiogenic challenge (6,11). However, there have been conflicting reports regarding the robustness of the AS phenotypes observed (22).…”
mentioning
confidence: 99%